낮보호 시설에 대한 차세대 노인들의 인식에 관한 연구 - 정연강(Yeoun Kang Chung); 염순교(Soon Gyo Yeoum); 권혜진(Hye Jin Kwon); 김경희(Kyung Hee Kim); 김인국(In Kook Kim) (지역사회간호학회지, 1998)
This study describes the extent of recognition of problems to the aged in a future society, the recognition and necessity of day care facilities, and the service contents and patterns preferred as a method of mediation for nursing the aged and increasing their quality of life. It also tries to certify the relations between those subjects. The result of the study is as follows: 1. Concerning problems of the aged of social significance the aged of the next generation consider the difficulties in nursing the aged to be the most important at 63.6%. 2. Concerning the nursing of parents, 49.4% of those answered 'children should take care of their parents and live together', while 46.7% answered that 'it is enough for children to provide an economic support, not necessarily living together. 3. Concerning information of day care facilities, 66.9% answered that they have no information. 4. Concerning the use of day care facilities, 54.6% answered that 'they would under certain circumstances', and 21.0% that 'they had better use them in the future'. 5. Concerning the feelings of the aged using day care facilities, 46.6% say 'they do not look poor', and 33.4% said that 'they look a little poor'. 6. Concerning the reasons for using day care facilities, 56.1% answered' because children do not proride care', and 48.5% answered 'because their economic ability is not sufficient'. 7. Concerning the programs potentially needed, food supply, medical services and physical therapy were ranked in that order. 8. Concerning social facilities necessary for the aged, centers that specialize in dementia, free day care facilities, home care services, and fee - based day care centers were ranked in that order. 9. Concerning institutions providing day care, welfare centers for the aged, those centers auxiliary to hospitals, asylums, and individuals were ranked in that order. 10. Concerning the responsibity running day care facilities, social workers, doctors/nursing assistants, nurses, and entrusted visitors were ranked in that order. Based on the results of this study, the study proposes that the study of applied cases of therapy in day care facilities for the aged continue.